2018
DOI: 10.1038/bjc.2017.429
|View full text |Cite|
|
Sign up to set email alerts
|

Prostate-specific antigen velocity in a prospective prostate cancer screening study of men with genetic predisposition

Abstract: Background:Prostate-specific antigen (PSA) and PSA-velocity (PSAV) have been used to identify men at risk of prostate cancer (PrCa). The IMPACT study is evaluating PSA screening in men with a known genetic predisposition to PrCa due to BRCA1/2 mutations. This analysis evaluates the utility of PSA and PSAV for identifying PrCa and high-grade disease in this cohort.Methods:PSAV was calculated using logistic regression to determine if PSA or PSAV predicted the result of prostate biopsy (PB) in men with elevated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Using other biomarkers to determine an individual's risk of developing prostate cancer has been a relatively new approach and has not yet been applied in general population screening; however, many RNA, DNA, and proteinbased biomarkers in the urine, blood, and tissue samples have been studied to help predict the risk of prostate cancer [47][48][49][50][51][52][53][54][55][56][57]. Other tools or approaches for screening (coupled with PSA) for identifying adults at elevated risk include multiparametric magnetic resonance imaging (mpMRI), PSA velocity (PSAV), or risk calculators such as the Stockholm-3 model (S3M or STHLM3) [58][59][60][61]. PSA density, the PSA value (in ng/ml) divided by prostate volume (in CC), is another strategy used to predict prostate cancer, but has not been consistent in daily clinical practice over the years [62].…”
Section: Alternative Strategiesmentioning
confidence: 99%
“…Using other biomarkers to determine an individual's risk of developing prostate cancer has been a relatively new approach and has not yet been applied in general population screening; however, many RNA, DNA, and proteinbased biomarkers in the urine, blood, and tissue samples have been studied to help predict the risk of prostate cancer [47][48][49][50][51][52][53][54][55][56][57]. Other tools or approaches for screening (coupled with PSA) for identifying adults at elevated risk include multiparametric magnetic resonance imaging (mpMRI), PSA velocity (PSAV), or risk calculators such as the Stockholm-3 model (S3M or STHLM3) [58][59][60][61]. PSA density, the PSA value (in ng/ml) divided by prostate volume (in CC), is another strategy used to predict prostate cancer, but has not been consistent in daily clinical practice over the years [62].…”
Section: Alternative Strategiesmentioning
confidence: 99%
“…The IMPACT study evaluated PSA screening in men with a known genetic PCa predisposition due to BRCA1/2 mutations and found that a value of PSA >3 ng/mL is more strongly predictive in BRCA carriers than noncarriers [ 16 , 88 ].…”
Section: Genetic Counselling Guidelines For Genetic Test and Survmentioning
confidence: 99%
“…In a multicenter study concerning early diagnosis for men carrying BRCA2 mutations, systematic PSA screening was recommended (Figure 3) [87]. The IMPACT study evaluated PSA screening in men with a kno predisposition due to BRCA1/2 mutations and found that a value of P more strongly predictive in BRCA carriers than noncarriers [16,88].…”
Section: Genetic Counselling Guidelines For Genetic Test and Surveillmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoewel het hier ging om een trend en er nog geen significant verschil kon worden aangetoond met de controlegroep, was de verwachting dat dit met grotere aantallen en een langere follow-upperiode wel significant zou kunnen worden [6]. Daarnaast is ook aangetoond dat PSA-screening meer prostaatcarcinomen vindt bij BRCA1 en BRCA2 dragers dan bij nietdragers [8].…”
Section: De Impact-studieunclassified